Antiinflammatory Activity of Some New 3-(2H-1-benzopyran-2´ -one-3´ -yl)-5- Substituted Aryl Isoxazolines - Imran, Mohd.; A. Khan, Suroor (Asian Journal of Chemistry, 2010)
Newer isoxazoline derivatives were synthesized by condensing novel chalconcs with hydroxylamine hydrochloride in neutral medium. All the compounds were characterized on the basis of IR and 1H NMR spectral data. The compounds were evaluated for antiinflammatory activity against carrageenan induced rat paw edema and all the compounds showed significant antiinflammatory activity.